Cultural Considerations for using Emotionally Focused Therapy with African American Couples. Issue 2 (3rd April 2023) - Young, Jennifer; Tadros, Eman; Gregorash, Alexis
ABSTRACT: Emotionally Focused Therapy (EFT) is a theoretical approach that is considered widely effective in decreasing relationship distress among couples. Emotionally Focused Therapy uses deepening of the clients' emotions to facilitate change to break negative interactional patterns within couple relationships. However, African American men have developed some behaviors and attitudes about emotions that may present challenges to them receiving Emotionally Focused Therapy. Some of those behaviors and beliefs include alexithymia and emotion ideologies which include restricting emotion based on their experience with societal stressors (e.g., race-based trauma, system racism). Given this emotional discrepancy, there are social and cultural considerations that need to be addressed between African American individuals in order to conduct effective couple work. This paper discusses emotional expressiveness and culturally sensitive approaches that EFT therapists will need to consider when counseling African American men in couples therapy.